Pemanfaatan Congklak Musi KPK dan FPB untuk Meningkatkan Motivasi Belajar Numerasi Siswa SMP melalui Program Kampus Mengajar Angkatan 4 - Erwin Randjawali; Agnes Yuniati Malo; Vindya Donna Adindarena; Ririn Esna Saingo; Bellavista Paulina Luhi; Darius Imanuel Wadu; Yuliana Tamu Ina Nuhamara (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Technology adaptation assistance in schools is carried out in the form of applying math teaching aids, namely the Congklak Musi KPK and FPB. This activity was carried out by Unkriswina Sumba students together with lecturers through the Teaching Campus 4 program at Satap Padadita Public Middle School. The purpose of this activity is to demonstrate the use of the congklak musi KPK and FPB teaching aids in order to increase students' motivation to learn numeracy. The result of this activity is that the congklak math teaching aid can be made using used materials, and has been applied in the mathematics learning process in class VII, namely on KPK and FPB material. In addition, students are motivated to learn numeracy by using these teaching aids, and can improve students' ability to solve questions related to FPB and KPK.